Low-temperature denitration MgMn2O4 spinel catalyst as well as preparation method and application thereof

A low-cost, non-toxic MgMn2O4 spinel catalyst with a hollow quadrangular prism morphology addresses the challenges of existing catalysts by providing a novel MgMn2O4 spinel catalyst with a hollow quadrangular prism morphology, achieving high NO conversion rates and broad industrial applicability.

CN119140091APending Publication Date: 2024-12-17WUHAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310709856.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing ammonia selective catalytic reduction (NH3-SCR) catalysts, such as V2O5-WO3/TiO2, have high reaction temperatures, narrow temperature windows, poor low-temperature denitrification efficiency, and biotoxicity, making them unsuitable for industrial applications like cement rotary kilns and glass melting furnaces, and transition metal-based manganese spinels are expensive and scarce.

Method used

A low-temperature MgMn2O4 spinel catalyst with a hollow quadrangular prism morphology is prepared using a hydrothermal method with hexadecyltrimethylammonium bromide as a dispersant and oxalic acid or sodium oxalate, ensuring stoichiometric ratios and a porous structure for enhanced catalytic activity.

Benefits of technology

The catalyst exhibits high NO conversion rates above 80% at 120-300°C, is non-biotoxic, and cost-effective, with a broad application in industrial flue gas denitrification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004287323570000011
    Figure HDA0004287323570000011
  • Figure HDA0004287323570000012
    Figure HDA0004287323570000012
  • Figure HDA0004287323570000021
    Figure HDA0004287323570000021
Patent Text Reader

Abstract

The invention discloses a low-temperature denitration MgMn2O4 spinel catalyst as well as a preparation method and application thereof. The catalyst has the shape of a hollow quadrangular prism, and is prepared by dispersing magnesium salt and manganese salt by using hexadecyl trimethyl ammonium bromide as a dispersing agent, then mixing with oxalic acid or sodium oxalate, carrying out hydrothermal reaction at 140-160 DEG C, carrying out vacuum drying on a reaction product, and calcining in an oxidizing atmosphere. When the catalyst is used for low-temperature denitration, the low-temperature catalytic effect is remarkable, and the catalyst is free of biological toxicity, low in cost, simple in preparation method and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial catalysts, and in particular relates to a low-temperature denitration MgMn2O4 spinel catalyst and a preparation method and application thereof. Background Art

[0002] Nitrogen oxides (NO x ) is one of the main atmospheric pollutants, which can cause a series of environmental problems such as acid rain, haze and photochemical smog. Ammonia selective catalytic reduction (NH3-SCR) has become the mainstream technology for controlling nitrogen oxide emissions because of its relatively mature and efficient technology. The traditional commercial catalyst of this technology is V2O5-WO3 / TiO2, and it has been widely used in coal-fired power plants, but its reaction temperature is high (300-400℃), which makes it difficult to directly use it in the flue gas generated by cement rotary kilns, glass melting furnaces, metallurgical sintering machines, etc. in non-electric industries. In addition, V2O5-WO3 / TiO2 also has the disadvantages of narrow temperature window, poor low-temperature denitrification efficiency, and biotoxicity of the catalyst. Therefore, it is of great practical significance to find a new, efficient and environmentally friendly low-temperature NH3-SCR catalyst.

[0003] Spinel (AB2O4) is usually a compound composed of AO tetrahedron and BO octahedron. And due to its precise structure and composition, spinel plays an important role in the field of catalysis. Manganese oxide has excellent low-temperature SCR activity due to its variable valence state and excellent redox performance. Therefore, manganese-based spinel, as a material with a special structure, is an effective component for constructing low-temperature denitrification catalysts.

[0004] At present, the second active component of manganese-based spinel as denitrification catalyst is usually transition metal elements, such as MnCr2O4, Co x Mn 3-x O4, NiMn2O4, CuMn2O4, etc. Although these components help manganese to produce better denitrification activity at low temperatures, they are biotoxic, and transition metals are expensive and have limited resources. Therefore, there is an urgent need for a green and environmentally friendly manganese-based spinel with cheap and readily available raw materials for catalytic denitrification. Summary of the invention

[0005] The present invention aims to provide a low-temperature denitration MgMn2O4 spinel catalyst and its preparation method and application in view of the deficiencies in the prior art. The low-temperature catalytic effect is significant, the catalyst itself is non-biotoxic, low-cost, simple in preparation method, and has broad application prospects.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0007] Provided is a low-temperature denitration MgMn2O4 spinel catalyst having a hollow quadrangular prism morphology.

[0008] According to the above scheme, the catalyst is prepared by dispersing magnesium salt and manganese salt with hexadecyltrimethylammonium bromide as a dispersant, then mixing with oxalic acid or sodium oxalate to undergo a hydrothermal reaction at 140-160°C, and the reaction product is vacuum dried and calcined in an oxidizing atmosphere.

[0009] Provided is a method for preparing the above-mentioned low-temperature denitration MgMn2O4 spinel catalyst, comprising the following steps:

[0010] 1) dissolving dispersant hexadecyltrimethylammonium bromide in deionized water to obtain a dispersant solution, dispersing magnesium salt and manganese salt in the dispersant solution to obtain a mixture A; dissolving oxalic acid or sodium oxalate in deionized water to obtain a solution B;

[0011] 2) under stirring, adding solution B dropwise into mixture A to obtain suspension C, and performing a hydrothermal reaction at 140-160° C.;

[0012] 3) The hydrothermal reaction product of step 2) is vacuum dried and then calcined in an oxidizing atmosphere to obtain a low-temperature denitration catalyst.

[0013] According to the above scheme, in step 1), the magnesium salt is magnesium nitrate, magnesium acetate, magnesium chloride or magnesium carbonate; the manganese salt is manganese nitrate, manganese acetate, manganese chloride or manganese carbonate.

[0014] Preferably, when oxalic acid is selected, the magnesium salt is selected as magnesium acetate or magnesium carbonate, and the manganese salt is selected as manganese acetate or manganese carbonate; when sodium oxalate is selected, the magnesium salt is selected as magnesium nitrate or magnesium chloride, and the manganese salt is selected as manganese nitrate or manganese chloride.

[0015] When oxalic acid is selected, magnesium salt and manganese salt are selected from weak acid salts such as acetate or carbonate. When they are dissolved in deionized water, the ionized metal ions and weak acid radical ions are partially hydrolyzed to produce metal hydroxide and corresponding weak acid. When oxalic acid is added, on the one hand, the hydrolysis of weak acid radicals and the ionization of oxalic acid are promoted, and on the other hand, the hydrolysis of metal ions is inhibited and combined with oxalate radicals, which effectively avoids the loss of metal ions, ensures the stoichiometric ratio of metal ions, and helps to stably crystallize into a tetragonal spinel structure without forming other phases.

[0016] When sodium oxalate is selected, magnesium salt and manganese salt are selected from strong acid salts such as nitrate or chloride, which ionize into metal ions and strong acid anions (nitrate, chloride) when dissolved in deionized water. When sodium oxalate is added, oxalate combines with metal ions, and the remaining sodium ions and strong acid anions provide a neutral environment in the solution. This avoids the loss of metal ions due to the hydrolysis of oxalate in a strong acid solution, thereby ensuring the stoichiometric ratio of metal ions and facilitating stable crystallization into a tetragonal spinel structure.

[0017] According to the above scheme, in step 1), the molar ratio of the metal element is Mg:Mn=1:2; the molar ratio of the metal element to the oxalate is (Mg+Mn):C2O4 2- =1:1-1:1.15.

[0018] According to the above scheme, in step 1), the metal ion concentration of mixture A is 0.30-0.80 mol / L; the concentration of solution B is 0.60-1.84 mol / L.

[0019] According to the above scheme, in step 1), the concentration of the dispersant solution is 0.2-3.0 g / L. A suitable concentration is conducive to achieving high dispersion.

[0020] According to the above scheme, in step 1), mixture A is prepared at a temperature of 30-60°C; solution B is prepared at a temperature of 30-60°C.

[0021] According to the above scheme, in step 2), the hydrothermal reaction time is 12-36 hours.

[0022] According to the above scheme, in step 3), the vacuum drying temperature is 60-80°C, and the vacuum drying time is 6-12h.

[0023] According to the above scheme, in step 3), the oxidizing atmosphere is a mixture of N2 and O2; preferably, the composition of the mixed atmosphere is O2 / (O2+N2)=0.15-0.30.

[0024] According to the above scheme, in step 3), the calcination temperature is 400-700°C, the calcination time is 3-5h, and the heating rate is 2-5°C / min.

[0025] The present invention prepares a MgMn2O4 spinel catalyst having a hollow quadrangular prism morphology, wherein:

[0026] The present invention selects hexadecyltrimethylammonium bromide as a dispersant. On the one hand, its critical micelle concentration is low, which can greatly reduce the surface tension of water, so that the ions in the solution are highly dispersed; on the other hand, it is an ionic surfactant, which is conducive to combining with ions and water in the solution respectively, regulating the combination form of the precursor, and is conducive to the catalyst being able to form a hollow quadrangular prism morphology. At the same time, the hydrothermal reaction temperature is 140-160°C. If the hydrothermal temperature is too low, the hydrothermal reaction is incomplete; if the hydrothermal temperature is too high, it is not conducive to the growth of crystals to form a special hollow quadrangular prism morphology. The hydrothermal product is vacuum dried and then calcined in an oxidizing atmosphere. On the one hand, it ensures that the Mn ions are not oxidized under vacuum drying, which is conducive to the formation of a spinel phase; on the other hand, calcination in an oxidizing atmosphere promotes the decomposition of oxalate and escapes in the form of gas, which is conducive to the formation of a spinel phase and a porous morphology.

[0027] Provide a low-temperature denitration MgMn2O4 spinel catalyst for removing nitrogen oxides (NO X ) in the application.

[0028] According to the above scheme, nitrogen oxides are removed from industrial flue gas; preferably, the nitrogen oxides are NO.

[0029] According to the above scheme, the specific application method includes the following steps: placing the catalyst in a reaction vessel, purging the reaction system with N2 until the air is exhausted, and then introducing a mixed gas containing industrial flue gas containing nitrogen oxides, NH3 and O2, and performing catalytic denitrification at a temperature of 80-300°C.

[0030] According to the above scheme, the component contents in the mixed gas are: 760-840ppm NH3, 680-760ppm NO and 2.85-3.15vol% O2.

[0031] According to the above scheme, the reaction space velocity is 32000-35400mL·g -1 ·h -1 .

[0032] The beneficial effects of the present invention are as follows:

[0033] 1. The present invention provides a MgMn2O4 spinel denitrification catalyst with a special hollow quadrangular prism morphology, which is helpful for exposing specific highly reactive crystal faces. It is used in catalytic denitrification, synergistically utilizing basic sites (Mg) and redox sites (Mn), and has a significant low-temperature catalytic effect. The catalyst itself is non-biotoxic, low-cost, and has broad application prospects.

[0034] 2. The present invention adopts a simple hydrothermal synthesis method to prepare a hollow quadrangular prism-shaped MgMn2O4 spinel low-temperature denitrification catalyst; wherein: the reaction is carried out in a solution with a highly dispersed ionic surfactant, and then coordinated with appropriate hydrothermal reaction conditions to allow the metal oxalate to grow into a hollow quadrangular prism in a certain form, and finally calcined, the oxalate decomposes and escapes in the form of gas, so that the catalyst forms a certain pore structure; the obtained catalyst has a large specific surface area and exhibits good denitrification activity at low temperatures. At the same time, the raw materials are cheap and easy to obtain, and the catalyst has low biological toxicity, which is conducive to industrial application.

[0035] 3. Furthermore, the combination of weak acid metal salts with oxalic acid and strong acid metal salts with sodium oxalate is beneficial to promote the combination of metal ions and oxalate, avoid the loss of metal ions, ensure the stoichiometric ratio, and stably crystallize into a tetragonal spinel structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the XRD pattern of the catalyst prepared in Example 1.

[0037] Figure 2 For Example 1 ( Figure 2 a) and Comparative Example 3 ( Figure 2 b) SEM image of the prepared catalyst.

[0038] Figure 3 The catalysts prepared in Example 1 and Comparative Examples 1-3 have denitration catalytic activity at 80-300°C. DETAILED DESCRIPTION

[0039] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0040] Unless otherwise specified in the following examples, the drugs used were all analytically pure and did not require further purification.

[0041] Example 1

[0042] A hollow quadrangular prism-shaped MgMn2O4 spinel catalyst for removing nitrogen oxides at low temperature is prepared by the following method:

[0043] 1) At a temperature of 50°C, first weigh 0.0900 g of hexadecyltrimethylammonium bromide and dissolve it in 100 mL of deionized water, then weigh 4.2891 g of Mg(CH3COO)2·4H2O and 9.8036 g of Mn(CH3COO)2·4H2O and completely disperse them in the above solution under vigorous stirring to obtain a mixture A, and then weigh 7.5642 g of H2C2O4·2H2O and dissolve it in 50 mL of deionized water to obtain a solution B.

[0044] 2) Then, solution B is slowly added dropwise to mixture A while stirring. After the addition is complete, the mixed solution C of A and B is transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140°C for 24 hours. After the autoclave is cooled naturally, the mixture is filtered through a circulating water vacuum pump and washed several times with deionized water, and then the filter cake is transferred to a vacuum drying oven and dried at 60°C for 12 hours.

[0045] 3) Finally, the powder was calcined in a tube furnace at 600°C for 4 h in an atmosphere of O2 / (O2+N2)=0.25, and then the calcined product was fully ground to obtain a MgMn2O4 spinel catalyst.

[0046] Figure 1 The XRD spectrum of the catalyst prepared in Example 1 shows that all diffraction peaks of the catalyst can be attributed to a tetragonal spinel structure with a space group of I41 / amd, corresponding to PDF#23-0392MgMn2O4.

[0047] Figure 2 (a) is a SEM image of the catalyst prepared in Example 1. The image shows that the catalyst morphology is a hollow quadrangular prism with a nearly regular rhombus cross section, and microporous structures exist on the surface and inside of the catalyst due to the generation of gas by decomposition of oxalate during calcination.

[0048] The denitration reaction test was carried out using the hollow quadrangular prism-shaped MgMn2O4 spinel catalyst prepared in Example 1:

[0049] The test was conducted in a homemade quartz tube (id20 mm) reactor (equipped with a temperature control and gas mixing system). 2.00 g of hollow quadrangular prism-shaped MgMn2O4 spinel catalyst was taken out and pressed into several small round beads and placed in the reactor. Before the test, the reaction system was purged with N2 until the air was exhausted, and then a mixed gas of 800 ppm NH3, 720 ppm NO, and 3 vol% O2 balanced with N2 was introduced, and a mass flow meter (Sevenstar CS300) was used to control the gas hourly space velocity (GHSV) to be maintained at 33600 mL·g -1 ·h -1 The test was conducted under the following conditions. During the test, the reaction temperature was raised from 80 to 300°C, and the concentration of the mixed gas in the reaction system was monitored in real time using a flue gas analyzer (FGA-10). Within the above reaction temperature range (80-300°C), a set of data was recorded at intervals of 20°C when the gas concentration was stable, and the denitrification activity at different temperatures was measured.

[0050] The conversion rate of NO is given by the formula ([NO] in –[NO] out ) / [NO] in× 100%, where “in” and “out” refer to the inlet and outlet concentrations of the reaction system, respectively.

[0051] like Figure 3 As shown, the results show that the NO conversion rate is maintained above 80% in the temperature range of 120-300°C, and the NO conversion rate can reach above 90% in the test temperature range of 160-280°C, that is, the catalyst exhibits good performance in low-temperature catalytic reduction of nitrogen oxides.

[0052] Comparative Example 1

[0053] A single magnesium oxide catalyst is prepared by the following method:

[0054] 1) At 50°C, first weigh 0.0900 g of hexadecyltrimethylammonium bromide and dissolve it in 100 mL of deionized water. Then weigh 12.8673 g of Mg(CH3COO)2·4H2O and completely disperse it in the above solution under vigorous stirring to obtain a mixture A. Then weigh 7.5642 g of H2C2O4·2H2O and dissolve it in 50 mL of deionized water to obtain a solution B.

[0055] 2) Then, solution B is slowly added dropwise to solution A while stirring. After the addition is completed, the mixed solution C of A and B is transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140°C for 24 hours. After the autoclave is cooled naturally, the mixture is filtered through a circulating water vacuum pump and washed several times with deionized water, and then the filter cake is transferred to a vacuum drying oven and dried at 60°C for 12 hours.

[0056] 3) Finally, the powder was calcined in a tube furnace at 600° C. in an atmosphere of O 2 / (O 2 +N 2 )=0.25 for 4 h, and then the calcined product was fully ground to obtain a single magnesium oxide catalyst.

[0057] Denitration reaction test was carried out using the single magnesium oxide catalyst prepared in Comparative Example 1:

[0058] The test was conducted in a homemade quartz tube (id20 mm) reactor (equipped with a temperature control and gas mixing system). 2.00 g of a single magnesium oxide catalyst was taken out and pressed into several small round beads and placed in the reactor. Before the test, the reaction system was purged with N2 until the air was exhausted, and then a mixed gas of 800 ppm NH3, 720 ppm NO, and 3 vol% O2 balanced with N2 was introduced, and a mass flow meter (Sevenstar CS300) was used to control the gas hourly space velocity (GHSV) to be maintained at 33600 mL·g -1 ·h -1During the test, the reaction temperature was raised from 80 to 300°C, and at the same time, the concentration of the mixed gas in the reaction system was monitored in real time using a flue gas analyzer (FGA-10).

[0059] The conversion rate of NO is given by the formula ([NO] in –[NO] out ) / [NO] in × 100%, where “in” and “out” refer to the inlet and outlet concentrations of the reaction system, respectively.

[0060] like Figure 3 As shown, the results show that there is almost no catalytic activity in the temperature range of 120-300℃, and NH3, NO and O2 simply react in hot air.

[0061] Comparative Example 2

[0062] A single manganese oxide catalyst is prepared by the following method:

[0063] 1) At a temperature of 50°C, first weigh 0.0900 g of hexadecyltrimethylammonium bromide and dissolve it in 100 mL of deionized water. Then weigh 14.7054 g of Mn(CH3COO)2·4H2O and completely disperse it in the above solution under vigorous stirring to obtain a mixture A. Then weigh 7.5642 g of H2C2O4·2H2O and dissolve it in 50 mL of deionized water to obtain a solution B.

[0064] 2) Then, solution B is slowly added dropwise to solution A while stirring. After the addition is completed, the mixed solution C of A and B is transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140°C for 24 hours. After the autoclave is cooled naturally, the mixture is filtered through a circulating water vacuum pump and washed several times with deionized water, and then the filter cake is transferred to a vacuum drying oven and dried at 60°C for 12 hours.

[0065] 3) Finally, the powder was calcined in a tube furnace at 600° C. in an atmosphere of O 2 / (O 2 +N 2 )=0.25 for 4 h, and then the calcined product was fully ground to obtain a single manganese oxide catalyst.

[0066] Denitration reaction test was carried out using the single manganese oxide catalyst prepared in Comparative Example 2:

[0067] The test was conducted in a homemade quartz tube (id20 mm) reactor (equipped with a temperature control and gas mixing system). 2.00 g of a single manganese oxide catalyst was taken out and pressed into a number of small round beads and placed in the reactor. Before the test, the reaction system was purged with N2 until the air was exhausted, and then a mixed gas of 800 ppm NH3, 720 ppm NO, and 3 vol% O2 balanced with N2 was introduced, and a mass flow meter (Sevenstar CS300) was used to control the gas hourly space velocity (GHSV) to be maintained at 33600 mL·g -1 ·h -1 During the test, the reaction temperature was raised from 80 to 300°C, and at the same time, the concentration of the mixed gas in the reaction system was monitored in real time using a flue gas analyzer (FGA-10).

[0068] The conversion rate of NO is given by the formula ([NO] in –[NO] out ) / [NO] in × 100%, where “in” and “out” refer to the inlet and outlet concentrations of the reaction system, respectively.

[0069] like Figure 3 As shown, the results show that although it exhibits certain reaction activity in the temperature range of 120-300°C, the NO conversion rate is very low, less than 40%.

[0070] Comparative Example 3

[0071] A MgMn2O4 spinel catalyst is prepared by the following method:

[0072] 1) At a temperature of 50°C, first weigh 0.0900 g of hexadecyltrimethylammonium bromide and dissolve it in 100 mL of deionized water, then weigh 4.2891 g of Mg(CH3COO)2·4H2O and 9.8036 g of Mn(CH3COO)2·4H2O and completely disperse them in the above solution under vigorous stirring to obtain a mixture A, and then weigh 7.5642 g of H2C2O4·2H2O and dissolve it in 50 mL of deionized water to obtain a solution B.

[0073] 2) Then, solution B is slowly added dropwise to mixture A while stirring. After the addition is complete, the mixed solution C of A and B is transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180°C for 24 hours. After the autoclave is cooled naturally, the mixture is filtered through a circulating water vacuum pump and washed several times with deionized water, and then the filter cake is transferred to a vacuum drying oven and dried at 60°C for 12 hours.

[0074] 3) Finally, the powder was calcined in a tube furnace at 600°C for 4 h in an atmosphere of O2 / (O2+N2)=0.25, and then the calcined product was fully ground to obtain a MgMn2O4 spinel catalyst.

[0075] Figure 2 (b) is a SEM image of the catalyst prepared in Comparative Example 3. The image shows that the catalyst morphology is irregular particles.

[0076] The denitration reaction test was carried out using the non-hollow quadrangular prism-shaped MgMn2O4 spinel catalyst prepared in Comparative Example 3:

[0077] The test was conducted in a homemade quartz tube (id20 mm) reactor (equipped with a temperature control and gas mixing system). 2.00 g of the catalyst was taken out and pressed into several small round beads and placed in the reactor. Before the test, the reaction system was purged with N2 until the air was exhausted, and then a mixed gas of 800 ppm NH3, 720 ppm NO, and 3 vol% O2 balanced with N2 was introduced, and a mass flow meter (Sevenstar CS300) was used to control the gas hourly space velocity (GHSV) to 33600 mL·g -1 ·h -1 During the test, the reaction temperature was raised from 80 to 300°C, and the concentration of the mixed gas in the reaction system was monitored in real time using a flue gas analyzer (FGA-10). A set of data was recorded every 20°C in the above reaction temperature range when the gas concentration was stable.

[0078] The conversion rate of NO is given by the formula ([NO] in –[NO] out ) / [NO] in × 100%, where “in” and “out” refer to the inlet and outlet concentrations of the reaction system, respectively.

[0079] like Figure 3 As shown, the results show that compared with Example 1, the overall denitration activity of the catalyst prepared by Comparative Example 3 is poor within the test range, especially in the low temperature range of 80-200°C, the NO conversion rate has a gap of 5-20%.

[0080] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.

Claims

1. A low temperature denitrification MgMn 2 O 4 Spinel catalyst, It is characterized in that It has the shape of a hollow quadrangular prism.

2. The catalyst according to claim 1, It is characterized in that The catalyst is prepared by dispersing magnesium salt and manganese salt using hexadecyltrimethylammonium bromide as a dispersant, then mixing with oxalic acid or sodium oxalate to carry out hydrothermal reaction at 140-160° C., and then calcining the reaction product in an oxidizing atmosphere after vacuum drying.

3. A method for preparing the catalyst according to claim 1, It is characterized in that The steps include: 1) dissolving dispersant hexadecyltrimethylammonium bromide in deionized water to obtain a dispersant solution, dispersing magnesium salt and manganese salt in the dispersant solution to obtain a mixture A; dissolving oxalic acid or sodium oxalate in deionized water to obtain a solution B; 2) under stirring, adding solution B dropwise into mixture A to obtain suspension C, and performing a hydrothermal reaction at 140-160° C.; 3) The hydrothermal reaction product of step 2) is vacuum dried and then calcined in an oxidizing atmosphere to obtain low-temperature denitrated MgMn 2 O 4 Spinel catalyst.

4. The preparation method according to claim 3, It is characterized in that In the step 1), the magnesium salt is magnesium nitrate, magnesium acetate, magnesium chloride or magnesium carbonate; the manganese salt is manganese nitrate, manganese acetate, manganese chloride or manganese carbonate.

5. The preparation method according to claim 4, It is characterized in that When oxalic acid is selected, the magnesium salt is selected as magnesium acetate or magnesium carbonate, and the manganese salt is selected as manganese acetate or manganese carbonate; when sodium oxalate is selected, the magnesium salt is selected as magnesium nitrate or magnesium chloride, and the manganese salt is selected as manganese nitrate or manganese chloride.

6. The preparation method according to claim 3, It is characterized in that In the step 1), the molar ratio of the metal element is Mg:Mn=1:2; the molar ratio of the metal element to the oxalate is (Mg+Mn):C 2 O 4 2- =1:1-1:1.15; the concentration of the dispersant solution is 0.2-3.0g / L.

7. The preparation method according to claim 3, It is characterized in that In the step 1), mixture A is prepared at a temperature of 30-60°C; solution B is prepared at a temperature of 30-60°C; In the step 2), the hydrothermal reaction time is 12-36h; In the step 3), the vacuum drying temperature is 60-80°C, and the vacuum drying time is 6-12h; the calcination temperature is 400-700°C, and the calcination time is 3-5h, and the heating rate is 2-5°C / min.

8. The preparation method according to claim 3, It is characterized in that In step 3), the oxidizing atmosphere is N 2 and O 2 of mixed gas.

9. A low-temperature denitrification MgMn according to claim 1 2 O 4 Application of spinel catalysts in the removal of nitrogen oxides.

10. The use according to claim 9, It is characterized in that The specific application method comprises the following steps: placing the catalyst in a reaction container, 2 The reaction system is purged until the air is exhausted, and then industrial flue gas containing nitrogen oxides, NH 3 and O 2 The mixed gas is catalytically denitrated at a temperature of 80-300℃.

Citation Information

Cited By

  • Preparation method and application of in-situ polymerization coated spinel MgMn2O4 positive electrode material

    CN120698507A